Abstract 14862: Gender Differences in Impact of CYP2C19 Polymorphism and Low Grade Inflammation on Coronary Microvascular Disease - Akasaka, Tomonori; Hokimoto, Seiji; Tabata, Noriaki; Sakamoto, Kenji; Tsujita, Kenichi; Kojima, Sunao; Kaikita, Koichi; Ogawa, Hisao (Circulation, 2014)
Abstract only Background: Specific CYPs localized in vascular smooth muscle and endothelium contribute to the regulation of vascular tone and homeostasis. CYP2C19 two loss-of-function alleles (PM) were found to be an independent risk factor for diabetic retinopathy, and PM is associated with the coronary spasm especially in female. However, it is unknown whether CYP2C19 genotype is associated with the coronary microvascular disease. The aim was to evaluate the impact of CYP2C19 genotype on coronary microvascular disease. Methods: We examined CYP2C19 genotype in patients with microvascular disease (n=40) who were diagnosed by intra-coronary acetylcholine infusion test and healthy subjects (n=455) as control group. We defined the coronary microvascular disease that have no epicardial spasm and have angina, ischemic ECG changes, reduced coronary blood flow, or inversion of lactic acid level between intra-coronary and coronary sinus. CYP2C19 genotypes were divided into 3 groups; (1) CYP2C19*1/*1: EM, (2) one loss-of-function allele (*1/*2, *1/*3: IM), and (3) two loss-of-function alleles (*2/*2, *2/*3, *3/*3: PM). Results: The ratios of CYP2C19 genotype (EM, IM, and PM) were 33, 35, and 32% in microvascular disease group, and 32, 49, and 19% in control group. In short, PM frequency was significantly higher in microvascular disease group (32%vs19%,P=0.039). In microvascular disease group, the ratios of CYP2C19 genotype (EM, IM, and PM) were 44, 38, and 19% in male, and 25, 33, and 42% in female, respectively. Briefly, the PM frequency was significantly higher in female than in male (42%vs19%,P=0.011). Moreover, the level of hs-CRP was significantly higher in microvascular disease group (0.37±0.908 vs 0.10±0.240, P<0.001). Multivariate analysis for microvascular disease indicated that gender, high age, smoking, hypertension, and the high level of hs-CRP are predictive factors among all subjects. PM is a predictive factor for microvascular disease in female group only (OR3.214, 95%RI 1.286-8.034, P=0.012), but not in male (OR0.909, 95%RI 0.251-3.285, P=0.884). Conclusion: The CYP2C19 two loss-of-function alleles (PM) and low grade inflammation may be associated with pathophysiology of coronary microvascular disease, especially in female.